GOVERNMENT OF INDIA CENTRAL MARINE FISHERIES RESEARCH STATION MANDAPAM CAMP ANNUAL REPORT OF THE CHIEF RESEARCH OFFICER FOR THE YEAR ENDING 31ST MARCH 1954 - Mandapam, CMFRS (Indian Journal of Fisheries, 2016)
THE year 1953-54 marked further progress in marine fisheries research workcarried out at the Headquarters Station at Mandapam, the Sub-Station atKozhikode and the Research Units at Karwar for mackerel, Cochin forprawn and at Madras for moUuscan fisheries. Programmes of work undertakenat the various centres of study were actively continued